Creating Trust and Reducing Consumers’ Risk Perception in Internet Shopping - Tian, Vane-Ing; Wong, Yu-sum Eugenia; Pang, Wai-Man (Journal of Marketing Development and Competitiveness, 2018)
The aim of this study is to suggest methods to create trust and reduce consumers’ risk perception in internet shopping. This study proposed a 2 x 2 experimental design to test the effectiveness of online consumer-generated rating and payment method in creating trust and reducing consumers’ risk perception in internet shopping. Findings of this paper provide empirical validation that a retailer with a favorable online consumer-generated rating is more effective than one without an online consumergenerated rating in building trust and having positive effects on the buying intention. Limitations, implications and directions for future research are also discussed.